2008
DOI: 10.1037/1076-898x.14.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Thinking graphically: Connecting vision and cognition during graph comprehension.

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 38 publications
2
48
1
Order By: Relevance
“…Gilhooly et al [8] found the use of "specialist schemata" in geographers' reading of contour maps, where visual patterns formed by several contour lines indicate some global structures in the area, such as valleys and interlocking spurs. Ratwani et al [21] distinguished "specific information" and "integrating information" that can be extracted from choro- Fig. 1.…”
Section: Problemmentioning
confidence: 99%
“…Gilhooly et al [8] found the use of "specialist schemata" in geographers' reading of contour maps, where visual patterns formed by several contour lines indicate some global structures in the area, such as valleys and interlocking spurs. Ratwani et al [21] distinguished "specific information" and "integrating information" that can be extracted from choro- Fig. 1.…”
Section: Problemmentioning
confidence: 99%
“…They are believed to assist in the recognition of patient deterioration, 14 particularly if they are in spectral colour palates. 15 Computer-based systems are used in around one in 12 London hospitals but have yet to be introduced to acute trusts in Scotland. The merits of computer-based systems are in the speed and accuracy of recording patient observations 16 and in the collation of data to validate and optimise the performance of TTS.…”
Section: Discussionmentioning
confidence: 99%
“…Different visual displays of the same information (i.e., informationally equivalent displays) can often yield drastically different task performance because different visual displays are not computationally equivalent (Carpenter & Shah, 1998;Gattis & Holyoak, 1996;Hegarty, Canham, & Fabrikant, 2010;Kroft & Wickens, 2002;Larkin & Simon, 1987;Ratwani, Trafton, & Boehm-Davis, 2008;Sanfey & Hastie, 1998). For example, two sets of informationally equivalent graphs were found to be computationally different, and the computational advantages of a new representation could even outweigh the disadvantages of unfamiliar representations (Peebles & Cheng, 2003).…”
Section: Spatial Organization Of Visual Information For Complex Tasksmentioning
confidence: 99%